An asymmetric iminium ion catalysis-enabled cascade cycloaddition reaction of chromone-oxindole synthons with enals: construction of a spirooxindole–hexahydroxanthone framework. Issue 36 (5th September 2019) - Zhang, Wen-Hui; Zhou, Yan-you; He, Xue-Wen; Gong, Yi; Liu, Xiong-Li; Zhou, Ying
Abstract : We report the first asymmetric iminium ion catalysis-enabled cascade cycloaddition reaction of bifunctional chromone-oxindole synthons and α, β-unsaturated aldehydes. Abstract : We report the first asymmetric iminium ion catalysis-enabled cascade cycloaddition reaction of bifunctional chromone-oxindole synthons and α, β-unsaturated aldehydes. This allowed one quaternary and four tertiary contiguous stereogenic centers to be constructed in a single operation. A range of spirooxindole–hexahydroxanthone molecules are obtained with up to 62% yield, >20 : 1 dr and >99% ee. This reaction has not only provided a new approach for constructing hexahydroxanthone-fused scaffolds by utilizing asymmetric iminium ion catalysis, but also advanced the chemistry of diversity-oriented synthesis based on bifunctional chromone synthons.